Reflection and transmission characteristics of bianisotropic slabs with(out) a soft and hard surface: clarification of the magnetic group of symmetry - Yin, Wen-Yan (2014)
10.1002/(SICI)1098-2760(19990605)21:53.0.CO;2-H